An Analysis of Factors That Influence The Performance of Online Transportation Online User (Gojek and Grab) in Madiun Regency - Sawitri, Risma; Mustofa, Rochman Hadi (Universitas Muhammadiyah Surakarta, 2024)
This research aims to find out the factors that influence customer satisfaction in using online transportation (Grab and Gojek). This research uses a quantitative analysis method with a survey design as a data collection tool. The facts and data obtained from the questionnaire will be tested using the structural analysis technique Equation Modeling (SEM). The population in this study is people who use the Grab and Gojek transportation applications in the city of Madiun who are in the unlimited population category. The sampling technique in this research is purposive sampling. The results of this research are: 1) Men with a frequency of using online transportation 1-3 times and spending more than IDR 50,000 compared to women, 2) security has a positive influence on satisfaction with using online transportation, 3) security is not proven to have a positive influence on user's decision to use online transportation, 4) Customization has a significant direct effect on satisfaction with using online transportation, 5) Customization has a significant direct effect on the decision to use online transportation, 6) Economic Value has a direct effect (direct effect) ) which is significant on satisfaction with using online transportation, 7) Economic Value has a significant direct effect on the user's decision to use online transportation, 8) Satisfaction with using online transportation has a significant direct effect on the user's decision to use online transportation.